Relationship Between Local Culture and Voter Rationality in the 2024 Electoral Contestation in Batu Bara Regency - Ahmad Khairuddin; Oman Sukmana; Tutik Sulistyowati (Gondang: Jurnal Seni dan Budaya, 2026)
This study examines the relationship between local culture and voter rationality in the electoral contestation in Batu Bara Regency. The research aims to analyze how local cultural values influence the political behavior of society in determining their choices during regional head elections. As a multiethnic region predominantly shaped by coastal Malay culture, Batu Bara Regency possesses strong social characteristics rooted in kinship relations, traditional leaders, religious authority, and socio-political patronage networks. This study employs a qualitative method with approaches from political sociology and cultural anthropology. Data were collected through observation, in-depth interviews, and documentation studies involving community members, traditional leaders, religious figures, and local political campaign teams. The findings reveal that voter rationality in Batu Bara Regency is not entirely rational-instrumental as described in modern rational choice theory, but is significantly influenced by local culture, emotional proximity, ethnic identity, patron-client relations, and the legitimacy of traditional and religious leaders. Local culture functions as a medium for the production of political meaning that shapes voter preferences in electoral contestation. In this context, voting behavior represents a combination of pragmatic considerations and cultural values embedded within society. This study confirms that local democracy in Batu Bara Regency cannot be understood solely through formal political approaches, but must also be examined through the cultural dimensions that shape public political consciousness.